2017
DOI: 10.1364/ol.42.004699
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of underwater optical communications using spatial modes subjected to bubbles and obstructions

Abstract: Spatial modes have attracted increasing interest in free-space and fiber-based optical communications. Underwater wireless optical communication is becoming a promising technique in marine exploration. Here we investigate the underwater wireless optical communications using different spatial modes, i.e., traditional Gaussian modes, orbital angular momentum modes having helical phase fronts, and diffraction-free and obstruction-tolerant Bessel modes. We evaluate the underwater transmission performance of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Under a weak oceanic turbulence regime, Wang et al derived analytical formulas for the channel capacity and symbol error rate (SER) for OAM channels [239]. In Table IV, we summarizes the main experimental studies investigating the impact of underwater conditions on OAM modes covering mainly scattering, thermally induced turbulence, water turbidity and air-bubbles [135], [241], [243]- [245]. We note that the ranges of all the presented investigations from the literature are limited, which is not consistent with real-life applications requiring propagation distances up to tens of meters.…”
Section: Underwater Propagation Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under a weak oceanic turbulence regime, Wang et al derived analytical formulas for the channel capacity and symbol error rate (SER) for OAM channels [239]. In Table IV, we summarizes the main experimental studies investigating the impact of underwater conditions on OAM modes covering mainly scattering, thermally induced turbulence, water turbidity and air-bubbles [135], [241], [243]- [245]. We note that the ranges of all the presented investigations from the literature are limited, which is not consistent with real-life applications requiring propagation distances up to tens of meters.…”
Section: Underwater Propagation Effectsmentioning
confidence: 99%
“…To overcome the effect of bubbles, it is possible to use Bessel Gaussian modes, instead of OAM LG modes, since they can self-heal while being obstructed during propagation. This may enhance the performance of the UWOC, as shown in [245]. The underwater turbulence mitigation techniques are still limited in comparison with free space; this may be partially explained by the novelty of the UWOC.…”
Section: E Underwater Turbulence Effects Mitigationmentioning
confidence: 99%
“…The model was mainly developed for Gaussian-profile beams. Different experimental studies on spatial modes considered underwater turbulence and reported significant impacts on the mode purity over different turbulence regimes [35]. The effect of turbulence has also been theoretically investigated in recent reports [36], [37].…”
Section: Underwater Propagationmentioning
confidence: 99%
“…To improve the transmission capacity, the mode-division multiplexing (MDM) with orbital angular momentum (OAM) modes, one subset of SDM, has gained increasing interest [14][15][16][17][18][19]. Recently, OAM has been introduced into underwater wireless optical communications [20][21][22][23][24] with impressive performance. OAM mode set is an option for MDM for the potentiality to accommodate infinite states with orthogonality.…”
Section: Introductionmentioning
confidence: 99%